(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Acne vulgaris is a chronic inflammatory disorder of the pilosebaceous unit that affects a significant proportion of adolescents and adults worldwide, leading to substantial physical, psychological, and social burden. Conventional acne management has traditionally relied on topical and systemic antibiotics, retinoids, and hormonal agents. However, increasing concerns regarding antibiotic resistance, treatment-related adverse effects, and variable patient responses have prompted the development of modern, mechanism-based therapeutic strategies.